Sinonasal malignancy: what’s new? - Götte, Karl; Hörmann, Karl (ORL, 2004)
Tumors of the nasal cavity are located at a complex anatomic site and show a huge histological diversity. Although dealing with a rare malignancy, the last decade has brought - besides new histological and clinical classifications - a variety of new insights into etiological agents, tumor biology and therapeutic concepts as well as valuable overviews of rare histological subtypes. This review tries to disentangle the different medical and scientific aspects of the most frequently encountered histological types of tumors in the nasal cavity and the paranasal sinuses. We concentrate on epidemiology, classification, etiology, cytogenetics and molecular genetics, outcome and prognosis as well as treatment modalities, as far as the past few years have brought considerable new insights. Our principal aim is to provide the clinician with important data from publications of the last decade.